Incidence and trends in workplace violence within emergency departments in the United Kingdom 2017–2022: an observational time series analysis - Donald, Neil; Lindsay, Tim (Frontiers in Public Health, 2023)
Background: Workplace violence (WPV) is a notable issue facing healthcare services and workers globally. WPV impacts upon the well-being of staff and can put healthcare provision at risk with detrimental effects on patient care. This study aims to investigate and quantify, at national and regional levels, the incidence and trends of WPV within emergency departments (EDs). Methods: We requested data relating to WPV from all 152 trusts with an ED in the United Kingdom from January 2017-March 2022. We applied interrupted time series and trend analysis to check for significant differences in WPV across the COVID-19 pandemic. Results: We conducted time series analysis on 58 million attendances and detected statistically significant increases in WPV in March 2020 - 5·06/100,000 attendances (95% CI 1·59/100,000-8·53/100,000 P<0·01) and May 2020 - 20·63/100,000 attendances (95% CI 9·39-31·87 P<0·01). Rises in incidents of 0·37/100,000 attendances per month (95% CI 0·21-0·53 P<0·0001) were found January 2017-March 2020. We analysed 96 million attendances for yearly trends, which revealed statistically significant increasing trends of WPV in London and North-West England (P<0·05), and physical WPV in the North West England (P<0·05). Conclusion: There have been dramatic increases in incidents of WPV in United Kingdom EDs over the last five years with concerning rises during the COVID- 19 period. Our findings highlight the potential to further demoralise a workforce already under significant strain, resulting in increased absences for physical or mental health and an exodus of staff. Therefore, trusts should ensure there are robust systems in place to protect and safeguard staff.